Biochar-induced changes in soil microbial communities: a comparison of two feedstocks and pyrolysis temperatures - Kracmarova-Farren, Martina; Alexova, Eliska; Kodatova, Anezka; Mercl, Filip; Szakova, Jirina; Tlustos, Pavel; Demnerova, Katerina; Stiborova, Hana (Environmental microbiome, 2024)
BACKGROUND: The application of a biochar in agronomical soil offers a dual benefit of improving soil quality and sustainable waste recycling. However, utilizing new organic waste sources requires exploring the biochar's production conditions and application parameters. Woodchips (W) and bone-meat residues (BM) after mechanical deboning from a poultry slaughterhouse were subjected to pyrolysis at 300 °C and 500 °C and applied to cambisol and luvisol soils at ratios of 2% and 5% (w/w). RESULTS: Initially, the impact of these biochar amendments on soil prokaryotes was studied over the course of one year. The influence of biochar variants was further studied on prokaryotes and fungi living in the soil, rhizosphere, and roots of Triticum aestivum L., as well as on soil enzymatic activity. Feedstock type, pyrolysis temperature, application dose, and soil type all played significant roles in shaping both soil and endophytic microbial communities. BM treated at a lower pyrolysis temperature of 300 °C increased the relative abundance of Pseudomonadota while causing a substantial decrease in soil microbial diversity. Conversely, BM prepared at 500 °C favored the growth of microbes known for their involvement in various nutrient cycles. The W biochar, especially when pyrolysed at 500 °C, notably affected microbial communities, particularly in acidic cambisol compared to luvisol. In cambisol, biochar treatments had a significant impact on prokaryotic root endophytes of T. aestivum L. Additionally, variations in prokaryotic community structure of the rhizosphere depended on the increasing distance from the root system (2, 4, and 6 mm). The BM biochar enhanced the activity of acid phosphatase, whereas the W biochar increased the activity of enzymes involved in the carbon cycle (β-glucosidase, β-xylosidase, and β-N-acetylglucosaminidase). CONCLUSIONS: These results collectively suggest, that under appropriate production conditions, biochar can exert a positive influence on soil microorganisms, with their response closely tied to the biochar feedstock composition. Such insights are crucial for optimizing biochar application in agricultural practices to enhance soil health.
Keywords: Biochar; Soil quality; Enzymatic activity; Microbial composition; Organic waste recycling